(untitled) (Revista Contexto & Saúde, 2026)
This study aimed to evaluate the perception of faculty regarding the influence of Emergency Remote Teaching (ERT) on the training of undergraduate dental students, with emphasis on theoretical learning, clinical skills development, and faculty-student interaction. This was a cross-sectional study conducted with faculty members teaching the final year of the Dentistry course at a private university in Curitiba, Brazil, using the focus group methodology. Five faculty members participated, with an age range between 34 and 52 years, a mean time since graduation of 19.2 ± 5.3 years, and a minimum of five years of teaching experience at the university. Qualitative analysis of the discourses led to the extraction of meaning units, and the convergence of interpretations established three main categories of analysis: a) the teaching-learning process in the context of ERT in Dentistry, b) the student and ERT in Dentistry, and c) the faculty member and ERT in Dentistry. It was observed that the academic performance of dental students was associated with the difficulty of adapting to ERT and the psychosocial issues involved in the pandemic scenario. The sudden incorporation of new technologies into the teaching-learning process imposed significant challenges on the adaptation of both faculty and students across higher education institutions (HEIs).